Kiribati : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This report describes recent economic developments in Kiribati. Developments over the decade through 1992 were characterized by a fall in real per capita income, as economic development was constrained by a shortage of skilled manpower, weak infrastructure, and remoteness from major international markets. However, inflation was held broadly in line with price increases in major trading partners. The overall external balance was in large surplus, as substantial trade deficits in part reflecting small export earnings were more than offset by service account surpluses and external grant receipts.